Film Translation Practices in the Silent Film World - Zanotti, Serenella (Journal of Audiovisual Translation, 2025)
This article explores the work and modus operandi of film translators in the late silent era, with a particular focus on the Italian context. By drawing on contemporary periodicals, censorship records, production documents, and other archival materials, the study delves into the intricate and multifaceted nature of the silent film translator’s craft, which extended well beyond the translation of on-screen text. It seeks to provide evidence supporting the view that silent film translation was indeed “a holistic process” (O’Sullivan & Cornu, 2019a, p. 16), encompassing not only the translation of title cards but also other transformative practices, ranging from film re-editing to more extensive reworkings. Charlie Chaplin’s Mutual comedies serve as a case study to explore film translation practices in the silent film world. The analysis reveals that, in Italy, these films were more than simply translated – they were re-functioned and transformed by appropriation. Lay summary This article looks at how films were translated during the last decade of the silent era. It shows that translating films in that period was not just about changing words on screen. Translators played a much bigger role – they sometimes edited or even completely reworked the films to better suit local audiences. Using contemporary periodicals, censorship files, and production notes, the study reveals that translating silent films was a complex job. It involved not only the translation of intertitles, but also creative decisions that could change the film’s meaning or structure. To illustrate this, the article examines how Charlie Chaplin’s comedies were handled in Italy. It shows that these films were more than simply translated – they were adapted and transformed through the addition of new elements absent from the original, and by emphasising humor over pathos in ways that could significantly change their original meaning.